2016
DOI: 10.5194/se-7-55-2016
|View full text |Cite
|
Sign up to set email alerts
|

Grazing effects on soil characteristics and vegetation of grassland in northern China

Abstract: Abstract. Large areas of grassland in the agro-pastoral region of northern China were converted into cropland for grain production, and the remaining grasslands are being overgrazed and seriously degraded. The objective of this study was to evaluate how reductions in grazing intensity affect the soil and vegetation characteristics in grasslands of northern China. Soil heterogeneity and vegetation characteristics were evaluated for ungrazed (UG), moderate grazing (MG), and heavy grazing (HG) sites. Grazing incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The existence of spatial heterogeneity due to grazing has been well recognized and investigated in natural ecosystems (Lin et al, 2010;Ren et al, 2015;Wang, Johnson, Rong, & Wang, 2016;Zhao et al, 2007Zhao et al, , 2011. Besides, pasture heterogeneity has been associated with increased ecosystem services such as biodiversity and soil conservation (Benton, Vickery, & Wilson, 2003;Sch€ onbach, Wan, Gierus, Bai, & M€ uller, 2011;Wang et al, 2016). Nevertheless, most anthropogenic management interventions toward agricultural intensification in the last decades have led to environmental homogenization (Adler, Raff, & Lauenroth, 2001;Foley et al, 2005).…”
mentioning
confidence: 99%
“…The existence of spatial heterogeneity due to grazing has been well recognized and investigated in natural ecosystems (Lin et al, 2010;Ren et al, 2015;Wang, Johnson, Rong, & Wang, 2016;Zhao et al, 2007Zhao et al, , 2011. Besides, pasture heterogeneity has been associated with increased ecosystem services such as biodiversity and soil conservation (Benton, Vickery, & Wilson, 2003;Sch€ onbach, Wan, Gierus, Bai, & M€ uller, 2011;Wang et al, 2016). Nevertheless, most anthropogenic management interventions toward agricultural intensification in the last decades have led to environmental homogenization (Adler, Raff, & Lauenroth, 2001;Foley et al, 2005).…”
mentioning
confidence: 99%
“…However, a further increase of grazing exclusion duration from 11 to 31 years did not increase SOC stocks. Wang, Johnson, Rong, & Wang, 2016), leading to increased plant biomass accumulation on the soil surface . The reduction in grazing pressure also leads to more belowground root biomass than aboveground biomass, and the increased root: Shoot ratio accelerates SOC accumulation (Liu, Liu, Wu, Wang, & Chen, 2014).…”
Section: Soil Carbonmentioning
confidence: 99%
“…Under the upper reaches of the Changjiang River climatic conditions, the upper line of allowed soil loss is 50 t/(km 2 a) for developing soil from limestone, whereas 100 t/(km 2 a) for developing soil from non-carbonaceous rock. Wei (1996) reported that the T values of the calcareous soil area in the karst area ranged from 0.522 to 1.285 t/(km 2 a); if the eluviation and normal erosion in soil-forming process were not considered, then the scope of the T value ranges from 3.24 to 8.10 t/(km 2 a). However, the soil loss tolerance of some parts of the argillaceous limestone, such as the non-pure carbonate rocks, can be increased to 16.2-40.5 t/(km 2 a), and the upper line of soil allowed loss is 50 t/(km 2 a) for the karst area (Wei, 1996).…”
Section: T Value Criteria In Different Regionsmentioning
confidence: 99%
“…Wei (1996) reported that the T values of the calcareous soil area in the karst area ranged from 0.522 to 1.285 t/(km 2 a); if the eluviation and normal erosion in soil-forming process were not considered, then the scope of the T value ranges from 3.24 to 8.10 t/(km 2 a). However, the soil loss tolerance of some parts of the argillaceous limestone, such as the non-pure carbonate rocks, can be increased to 16.2-40.5 t/(km 2 a), and the upper line of soil allowed loss is 50 t/(km 2 a) for the karst area (Wei, 1996). Li (2006) reported that with 49.67 mm ka −1 as the average weathering dissolving rate of carbonate rocks in Guizhou, the pedogenesis rates of different petrologic assemblages in carbonate area were calculated and used as the values of soil loss tolerance in carbonate areas.…”
Section: T Value Criteria In Different Regionsmentioning
confidence: 99%